Association Between Early Parental Death and Loneliness in Adulthood: A Community-Based Study in Southwest China - Peng, Anjiao; Lai, Wanlin; He, Shixu; Li, Wanling; Song, Tingting; Ji, Shuming; Zhao, Xia; Chen, Lei (Frontiers in Psychiatry, 2022)
Loneliness is an increasing public health problem which largely endangers physical and mental health. Compelling evidence has shown that early parental death was closely associated with many mental health disorders in adulthood, but whether it would increase the risk of loneliness is still unclear. In this large community-based study, we included 32 682 adult participants (20-93 years old) from Southwest China and used the 3-item short version of University of California, Los Angeles (UCLA) loneliness scale to identify participants with loneliness. A total of 1 975 participants reported loneliness, which made the prevalence of loneliness being 6.0% in Southwest China. Logistic regression was used to evaluate the association between early parental death and loneliness after adjusting for age, gender, educational level, marital status, smoking and drinking status, living status, and chronic diseases. We found that early parental death was significantly associated with loneliness (OR = 1.21, 95%CI, 1.03 -1.42). Sensitivity analysis excluding those with mental health disorders (796 participants) yielded similar results (OR = 1.26, 95%CI, 1.06 - 1.49). We also found that being younger, single, divorced or widowed, having higher educational levels, living alone, and having chronic disorders were associated with loneliness. We conclude that childhood parental death may be a risk factor for loneliness in adulthood, suggesting that early intervention are needed for affected children to prevent long-lasting neuropsychiatric detrimental effects.